Hydraulic analysis and structural design of damaged coastal groin in Mahatao, Batanes - Yu, Delwin T.
Philippines has been experiencing different typhoons throughout the year and with these climatic anomalies, coastal structures is in dire need for their safety. Mahatao, in the island of Batanes, Philippines, experienced a massive typhoon named Ferdie [Meranti] that caused the damage of a coastal groin in its western coastline. With this study, it aims to help the local government of Batanes evaluate the conditions of the western coastline of Mahatao, Batanes with respect to the typhoon's onslaught. Also with this study, the evaluation of the effectiveness of the coastal structure specifically the coastal groin in Mahatao will be assessed. Upon wave analysis simulation using REF/DIF 1, results show that the structure was not enough to protect the shore and reduce the damage caused by the typhoon, thus the design of a new one is needed. Several designs are calculated and presented which the people of the Mahatao can use to defend the shoreline from destructive effects of the any typhoon. Upon inspection of these designs, it can be seen that the groin made out of dolosse has the least amount of required volume of rocks because of the interlocking capacity of the dolosse. Also the toe layer volume is the biggest compared to the other layers because of the importance in protecting the toe structure.